Design of hybrid gradient porous surfaces with magnetic nanoparticles. (23rd July 2015) - de León, Alberto S.; Rodríguez-Hernández, Juan; Mazarío, Eva; Sánchez-Marcos, Jorge; Menéndez, Nieves; Herrasti, Pilar; Muñoz-Bonilla, Alexandra
Abstract: This article describes the preparation of hybrid gradient porous surfaces by using the breath figures approach. In a first step gradient porous surfaces were created from polymeric blends consisting of a linear polystyrene as major component and amphiphilic copolymers of poly(styrene- co -acrylic acid) as minor component. THF was used as solvent conducting to porous surfaces with a gradual variation of the pore size in a radial manner due to the long evaporation time. A detailed investigation of the influence of chemical composition of the copolymer (i.e. ratio styrene/acrylic acid) on the porous films was carried out. These films were successfully employed to prepare hybrid gradient surfaces by incorporating of magnetic nanoparticles inside the cavities. For this purpose two different strategies were explored. On one hand a magnetic nanoparticles aqueous suspension was placed on the porous surface with a magnet below the film, and subsequently the colloidal suspension was removed. Alternatively, the magnetic suspension was placed onto the surface and left until complete evaporation. A further step of peeling off the top layer also conducts to the decoration of the nanoparticles exclusively in the interior of the holes. Both strategies allow the preparation of hybrid surfaces with a variation of the content of magnetic nanoparticles magnetic inside the holes as a function of the radial position. Graphical abstract: Highlights: Gradient porous surfaces prepared by using the breath figures approach. Influence of the chemical composition of the amphiphilic copolymer on the morphology of the porous structures. Hybrid films obtained by incorporation of magnetic nanoparticles inside the pores of the films.